Anti-Social behavior and its relationship to the need to love at Baghdad University students (Journal of the College of Education for Women, 2019)
1. Anti-social behavior Baghdad University students.2. Know the differences in anti's social behavior according to gender, specialization.3. Know-the need for love at Bagdad University students.4. Know the relationship between anti-social behavior and the need to love.The research sample consisted of (100) students, the researcher numbers tools to measure anti behavior and the need to love.The results showed that college students have an anti-social behavior is weak and they need to love and there is no correlation between them Function relationship. Researcher has shown a number of recommendations and proposals.